Health system capacity to manage diabetic ketoacidosis in nine low-income and lower-middle income countries: a cross-sectional analysis of nationally representative survey data. (January 2023) - Matthews, Sarah; Coates, Matthew M.; Bukhman, Alice; Trujillo, Celina; Ferrari, Gina; Dagnaw, Wubaye Walelgne; Fénelon, Darius Leopold; Getachew, Theodros; Karmacharya, Biraj; Larco, Nancy Charles; Lulebo, Aimée M.; Mayige, Mary Theodory; et al.
Summary: Background: There has been increasing awareness about the importance of type 1 diabetes (T1D) globally. Diabetic ketoacidosis (DKA) is a life-threatening complication of T1D in low-income settings. Little is known about health system capacity to manage DKA in low- and lower-middle income countries (LLMICs). As such, we describe health system capacity to diagnose and manage DKA across nine LLMICs using data from Service Provision Assessments. Methods: In this cross-sectional study, we used data from Service Provision Assessment (SPA) surveys, which are part of the Demographic and Health Survey (DHS) Program. We defined an item set to diagnose and manage DKA in higher-level (tertiary or secondary) facilities, and a set to assess and refer patients presenting to lower-level (primary) facilities. We quantified each item's availability by service level in Bangladesh (Survey 1: May 22 2014–Jul 20 2014; Survey 2: Jul 2017–Oct 2017), the Democratic Republic of the Congo (DRC) (Oct 16 2017–Nov 24 2017 in Kinshasha; Aug 08 2018–Apr 20 2018 in rest of country), Haiti (Survey 1: Mar 05 2013–Jul 2013; Survey 2: Dec 16 2017–May 09 2018), Ethiopia (Feb 06 2014–Mar 09 2014), Malawi (Phase 1: Jun 11 2013–Aug 20 2013; Phase 2: Nov 13 2013–Feb 7 2014), Nepal (Phase 1: Apr 20 2015–Apr 25 2015; Phase 2: Jun 04 2015–Nov 05 2015), Senegal (Survey 1: Jan 2014–Oct 2014; Survey 2: Feb 09 2015–Nov 10 2015; Survey 3: Feb 2016–Nov 2016; Survey 4: Mar 13 2017–Dec 15 2017; Survey 5: Apr 15 2018–Dec 31 2018; Survey 6: Apr 15 2019–Feb 28 2020), Tanzania (Oct 20 2014–Feb 21 2015), and Afghanistan (Nov 1 2018–Jan 20 2019). Variation in secondary facilities' capacity and trends over time were also explored. Findings: We examined data from 2028 higher-level and 7534 lower-level facilities. Of these, 1874 higher-level and 6636 lower-level facilities' data were eligible for analysis. Availability of all item sets were low at higher-level facilities, where less than 50% had the minimal set of supplies, less than 20% had the full minimal set, and less than 15% had the ideal set needed to diagnose and manage DKA. Across countries in lower-level facilities, less than 14% had the minimal set of supplies and less than 9% the full set of supplies for diagnosis and transfer of DKA patients. No country had more than 20% of facilities with the minimal set of items needed to assess or manage DKA. Where data were available for more than one survey (Bangladesh, Senegal, and Haiti), changes in availability of the minimal set and ideal set of items did not exceed 15%. Tertiary facilities performed best in Haiti, Ethiopia, Malawi, Nepal, Senegal, Tanzania, and Afghanistan. Secondary facilities that were rural, public, and had fewer staff had lower capacity. Interpretation: Health system capacity to manage DKA was low across these nine LLMICs. Although efforts are underway to strengthen health systems, a specific focus on DKA management is still needed. Funding: Leona M. and Harry B. Helmsley Charitable Trust, and Juvenile Diabetes Research Foundation Ltd .